Hot Deformation Behavior of Novel Al-Cu-Y(Er)-Mg-Mn-Zr Alloys - Maxim G. Khomutov; Sayed M. Amer; Ruslan Yu. Barkov; Maria V. Glavatskikh; Alexander Yu. Churyumov; Andrey V. Pozdniakov (Metals, 2021)
The compression tests in a temperature range of 400–540 °C and strain rates of 0.1–15 s−1 were applied to novel Al-Cu-Y(Er)-Mg-Mn-Zr alloys to investigate their hot deformation behavior. The higher volume fraction of the intermetallic particles with a size of 0.5–4 µm in the alloys caused an increase in flow stress. Hyperbolic sine law constitutive models were constructed for the hot deformation behavior of Al-Cu-Y(Er)-Mg-Mn-Zr alloys. Effective activation energy has a higher value in the alloys with Er than in the alloys with Y. According to the processing maps, the temperature range of 420–480 °C and strain rates higher than 5 s−1 are the most unfavorable region for hot deformation for the investigated alloys. The deformation at 440 °C and 15 s−1 led to cracks on the surface of the sample. However, internal cracks were not observed in the microstructure after deformation. The optimum hot deformation temperatures were in a range of 500–540 °C and at strain rates of 0.1–15 s−1.